IMPLEMENTASI SISTEM QOUTA DAN LIMITASI BANDWIDTH MENGUNAKAN USER MANEGER PADA MIKROTIK ROUTER OS - Afrianda, Nanda; Suharyanto, Cosmas Eko (LPPM Universitas Putera Batam, 2021)
Good bandwidth management makes data access to the maximum the process of sending data is not disturbed and the smoothness of data becomes good in the process of sending data uninterrupted and smooth in accessing the internet. However, with a lage number of partners and customers, as is the company’s abillity to create more added value. good stable internet network in a provider, of course it can greatly support the process of selling services to consumers, of course it is very necessary in the process of accessing information in internet access, in this case a provider is needed in managing the bandwidth distribution system. While the number of customers is large, so a provider must be smart in dividing good bandwidth according to the prioritized customer capacity. The problem that will arise on internet network that do not apply bandwidth management is that all users who are connected to the same network will not get the same capacity and will cause network congestion which interferes with other data traffic so that they cannot maximize the data sending process.